PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR KOGNITIF SISWA PADA KONSEP USAHA DAN ENERGI DI KELAS X MIPA.3 SMAN 10 BENGKULU - Sherli Malinda; Nyoman Rohadi; Rosane Medriati (Kumparan Fisika, 2017)
This research aims to increase the activity, scientific attitude and student cognitive learning outcomes. Subjects in this research were all students of class X MIPA3 which amounted to 31 students. This research was conducted in four stages: planning, action implementation, observation, and reflection. The results of this research indicate that student learning activity on cycle I with average score of 21 (enough category), increased in cycle II to 24.5 (good category), increased in cycle III to 26.5 (good category) and increased again on IV cycle to 28 (good category). Scientific students' attitude score in cycle I is 3.91; Increased in cycle II to 4.02; Increased in cycle III to 4.20 and increased again in IV cycle to 4.36. The students' cognitive learning outcomes for the first cycle obtained an average of 72.87 with a classical learning completeness of 74.19%, increased in cycle II to 75.97 with 87.1% classical learning completeness, increased in cycle III to 79.58 with 93.55% classical learning completeness and increased again in the IV cycle to 89.68 with 100% complete classical learning. Based on the results of the study concluded that the application of discovery learning model increases the activity, scientific attitude and student cognitive learning outcomes.